Methodological aspects and challenges of the Online Cohort on Food Behavior and Mental Health (COCASa) of university professors and students during the COVID-19 pandemic (Research, Society and Development, 2021)
The social distance adopted to control COVID-19 forced universities to adhere to new strategies for carrying out academic activities and research which started to be developed in virtual spaces. The aim of this article is to describe the methodological aspects and main challenges faced for the implementation of the COCASa project, an online cohort study on eating behavior and mental health of professors and students of universities in Brazil. The study                 started in July 2020 and will follow participants for two years. Proportional stratified non-probabilistic sampling was adopted and to assess participants information scales, food surveys and structured questions prepared by the project team were used. Among the baseline participants, 4,074 students and 2,210 professors started the questionnaire and, respectively, 76.8% and 85.1% completed the questionnaire. In both groups, the highest participation was of women (professors: 66.7% and students: 76.2%) and residents in the Northeast (professors: 37% and students: 50.9%) and South (professors: 27.1% and students: 22.5%) of Brazil. The online survey expands the possibility of recruiting participants and reaches territorial limits with less demand for funding. During the COVID-19 pandemic, the use of the virtual environment became a viable and accessible strategy for the maintenance of research activities, constituting a likely trend to be adopted by the scientific community.